2020
DOI: 10.3390/en13174547
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Co-Digestion of Microalgae and Primary Sludge to Enhance Methane Yield from Temperature-Phased Anaerobic Digestion

Abstract: A two-stage temperature-phased mesophilic anaerobic digestion assay was carried out to study the interaction between various biological pretreatment conditions and the possible synergistic co-digestion of microalgae and primary sludge. The study of growth kinetics of the biochemical methane potential test revealed that a maximum of 36% increase in methane yield was observed from co-digestion of a substrate pretreated by thermophilic aerobic conditions (55 °C and HRT = 2 days) and an 8.3% increase was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In WWTPs, an AcoD option exists between sludge and microalgae or microalgae with other residues. Damtie et al (2020) obtained a 36% increase in CH 4 production when studying AcoD from biologically pre-treated algal biomass and primary sludge. Solé-Bundó et al (2019b) obtained a 65% increase in CH 4 production in the AcoD of microalgae with primary sludge and a generation of 4.5 times the energy consumed, whereas the microalgae mono-digestion AD generated 2.7 times the energy consumed.…”
Section: Anaerobic Co-digestionmentioning
confidence: 96%
“…In WWTPs, an AcoD option exists between sludge and microalgae or microalgae with other residues. Damtie et al (2020) obtained a 36% increase in CH 4 production when studying AcoD from biologically pre-treated algal biomass and primary sludge. Solé-Bundó et al (2019b) obtained a 65% increase in CH 4 production in the AcoD of microalgae with primary sludge and a generation of 4.5 times the energy consumed, whereas the microalgae mono-digestion AD generated 2.7 times the energy consumed.…”
Section: Anaerobic Co-digestionmentioning
confidence: 96%
“…Vassalle et al [179] and Beltran et al [178] concluded that mixing 30 w/w% and 25 w/w% of microalgae with SS increased the methane production by 25% and 22%, respectively. However, many studies reported that ACoD of SS and microalgae reduces the process performance and efficiency [175,177,180]. According to Goncalves et al [181] and Olsson et al [182], adding 20 w/w% and 40 w/w% microalgae as co-substrate decreased specific methane production by 5% and 26% compared to SS mono-digestion.…”
Section: Overall Process Performancementioning
confidence: 99%
“…From Table 3 it can be seen that low thermal pretreatments (60-55°C; 1−2d) have none or very little effect on AcoD [19,86], however, when the temperature increased to 120°C, the biomethane production improve greatly (up to 43%) [18,49]. Other successfully tested pretreatments are ultrasonication, hot water, and a combination of thermal and alkaline pretreatments [57,71].…”
Section: Effect Of Pretreatmentsmentioning
confidence: 99%